Photonuclear method of production Cu-67 - Aizatskyi, N.I.; Dikiy, N.P.; Dovbnya, A.N.; Dolzhek, M.A.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V. (Вопросы атомной науки и техники, 2014)
The efficiently separation of ⁶⁷Cu is achieved by using diantipyrylpropylmethane (DАPPМ). Experimental separation of ⁶⁷Cu from sulphuric solution (1 mol./L) of zinc (2 mol./L) with addition potassium iodide (0.1 mol./L) is realized with help DAPPM (0.02 mol./L), which dissolve in chloroform. The 84.4% ⁶⁷Сu was extracted from water phase of ZnSO₄ into organic phase (solution DAPPM in chloroform). The ⁶⁷Cu remainder in organic phase is 4.6%. Effective extraction of protonated forms of reagent and ionic associate of metal+halide was realized by means of antipyrin forms in acid halide solution. The decrease of acidity of a water phase is necessary for effective reextraction. Re-extraction was realised by means of consecutive washing of organic phase (DAPPM in chloroform) by means of distilled water. Some amount of ZnSO₄ in process of extraction gets in organic phase that causes a low level re-extraction in first two tests. These tests re-extraction have low values рН. Re-extraction ⁶⁷Cu from solution DAPPM in chloroform is carried out consistently four times by distilled water. The activity of ⁶⁷Cu in third and fourth re-extraction tests was 72.7%. Экстракция диантипирилпропилметаном (ДАППМ) позволяет эффективно выделять ⁶⁷Cu. Реализовано экспериментальное выделение ⁶⁷Cu из сернокислого раствора (1 моль/л) цинка (2 моль/л) с добавлением йодистого калия (0,1 моль/л) при помощи ДАППМ (0,02 моль/л), растворенного в хлороформе. При экстракции ⁶⁷Сu из водной фазы ZnSO₄ переходит в органическую фазу (раствор ДАППМ в хлороформе) 84,4% ⁶⁷Сu. В органической фазе остается 4,6% ⁶⁷Сu. Производные антипирина образуют в кислых галогенидных растворах хорошо экстрагирующиеся ионные ассоциаты металл + галогенидного аниона и протонированной формы реагента. Поэтому для эффективной реэкстракции необходимо снижение кислотности водной фазы, что и реализуется при последовательных перемешиваниях органической фазы (ДАППМ в хлороформе) с дистиллированной водой. Некоторое количество ZnSO₄ в процессе экстракции попадает в органическую фазу, что обуславливает низкую степень реэкстракции в первых двух пробах. Эти пробы реэкстракции имеют низкие значения рН. Реэкстракцию ⁶⁷Сu из раствора ДАППМ в хлороформе проводили последовательно четыре раза дистиллированной водой. В третью и четвертую пробы реэкстрагировалось 72,7% активности ⁶⁷Сu. Екстракція діантіпірілпропілметаном (ДАППМ) дозволяє ефективно виділяти ⁶⁷Cu. Реалізовано експериментальне виділення ⁶⁷Cu з сірчанокислого розчину (1 моль/л) цинку (2 моль/л) з додаванням йодистого калію (0,1 моль/л) за допомогою ДАППМ (0,02 моль/л), розчиненого в хлороформі. При екстракції ⁶⁷Cu з водної фази ZnSO₄ переходить в органічну фазу (розчин ДАППМ в хлороформі) 84,4% ⁶⁷Cu. У органічній фазі залишається 4,6% ⁶⁷Cu. Похідні антипірину утворюють у кислих галогенідних розчинах добре екстрагуючі іонні асоціати метал + галогенідні аніони і протоновану форми реагенту. Тому для ефективної реекстракції необхідне зниження кислотності водної фази, що і реалізується при послідовних перемішуваннях органічної фази (ДАППМ в хлороформі) з дистильованою водою. Деяка кількість ZnSO₄ в процесі екстракції потрапляє в органічну фазу, що обумовлює низьку ступінь реекстракції в перших двох пробах. Ці проби реекстракції мають низькі значення рН. Реекстракції ⁶⁷Cu з розчину ДАППМ у хлороформі проводили послідовно чотири рази дистильованою водою. У третю і четверту проби реекстрагувалося 72,7% активності ⁶⁷Cu